Capitalism and the information age : the political economy of the global communication revolution - McChesney, Robert Waterman, 1952-; Wood, Ellen Meiksins; Foster, John Bellamy (New York, NY : Monthly Review Press, 1998)
Are the new technologies of the information age reshaping the labor force, transforming communications, changing the potential of democracy, and altering the course of history itself? Capitalism and the Information Age presents a rigorous examination of some of the most crucial problems and possibilities of these novel technologies. Not a day goes by that we don't see a news clip, hear a radio report, or read an article heralding the miraculous new technologies of the information age. The communication revolution associated with these technologies is often heralded as the key to a new age of'globalization.' How is all of this reshaping the labor force, transforming communications, changing the potential of democracy, and altering the course of history itself? Capitalism and the Information Age presents a rigorous examination of some of the most crucial problems and possibilities of these novel technologies.
Includes bibliographical references and index.
Keywords: Information technology -- Social aspects; Computers -- Social aspects; Capitalism